Comparing the needs and preferences of patients with moderate and severe dry eye symptoms across four countries. Issue 1 (15th December 2019) - Messmer, Elisabeth; Chan, Colin; Asbell, Penny; Johnson, Gary; Sloesen, Brigitte; Cook, Nigel
Abstract : Background/aims: Understanding patients' perspectives of their disease can inform drug development and treatment decisions. In this study, we compared the preferences and needs of patients with moderate and severe dry eye symptoms from four different countries. Methods: A quantitative questionnaire was developed based on the self-explicated conjoint methodology and was administered to 160 patients with moderate or severe dry eye disease (DED) from Australia, Germany, UK and the USA. Results: Patients with moderate dry eye symptoms ranked 'treatment satisfaction' as the most important aspect, whereas 'symptom bother' was more relevant for those in the severe group. Both the moderate and severe groups classified treatment effectiveness as the most important treatment attribute. This result was consistent across the four countries, although US patients gave significantly higher scores than patients from other countries (p<0.001). Furthermore, patients from Australia ranked 'treatment experience' as significantly more important than the concern of side effects, whereas respondents from Germany exhibited the opposite trend (p<0.05 for both). The health burden of DED is reflected in the average European Quality of Life-5 Dimensions 5-level (EQ-5D) scores of 0.764 and 0.658 for patients with moderate and severe disease, respectively. Conclusion: Our results confirm that across the countries in the study, moderate and severe DED has a major impact on patients' quality of life and daily activities. By providing insight into the patient perspective of DED, our study helps identify outcomes that are important to patients and may guide future drug development and clinical decision-making.